2000
DOI: 10.1007/s004210050054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanomyographic and electromyographic responses during fatigue in humans: influence of muscle length

Abstract: Mechanomyography (MMG) provides a measure of muscle mechanical changes during contractions. The purpose of this study was to quantify alterations in MMG signals during fatigue at two muscle lengths. Comparisons with electromyographic (EMG) recordings were made. A group of 13 subjects performed isometric dorsiflexions (50% of maximum for 60 s) at 40 degrees of plantarflexion (long, l(l)) and 5 degrees of dorsiflexion (short, l(s)). The mean power frequency of the EMG (f(EMG)) and MMG (f(MMG)) signals and the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 53 publications
3
68
1
Order By: Relevance
“…Various studies have linked fatigue occurrence to muscle length (which is dependent upon the joint angle) based on force loss in the muscle [4,5]. In addition, other researchers have found that the rate of fatigue in long muscles is dependent upon the rate of changes in the signal for both sEMG [6,7] and in the MMG signal [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have linked fatigue occurrence to muscle length (which is dependent upon the joint angle) based on force loss in the muscle [4,5]. In addition, other researchers have found that the rate of fatigue in long muscles is dependent upon the rate of changes in the signal for both sEMG [6,7] and in the MMG signal [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, MMG is the sound generated by a muscle during its contraction and is used as a measure of mechanical muscle changes during contraction [17]. Recently, it has been widely analyzed along with EMG for different purposes [18][19][20], such as control of a prosthesis with 2 degrees of freedom [21]. However, MMG can be affected by many factors, such as muscle temperature [22], skinfold thickness [23], and external mechanical noise [24].…”
Section: Introductionmentioning
confidence: 99%
“…1); our findings were in good agreement with those of previous investigations (Basmajian and De Luca, 1985;De Luca, 1984). With respect to EMG, the well-documented increase in amplitude during fatigue at different force levels has often been attributed to increase in MU recruitment and firing rate (Moritani et al, 1986;Weir et al, 2000). The decreases in MPF of EMG have been suggested to result from a decrease in muscle fiber conduction velocity (Sadoyama et al, 1983;Eberstein and Beattie, 1985), and possibly from an increase in MU synchronization (Weir et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to EMG, the well-documented increase in amplitude during fatigue at different force levels has often been attributed to increase in MU recruitment and firing rate (Moritani et al, 1986;Weir et al, 2000). The decreases in MPF of EMG have been suggested to result from a decrease in muscle fiber conduction velocity (Sadoyama et al, 1983;Eberstein and Beattie, 1985), and possibly from an increase in MU synchronization (Weir et al, 2000). However, synchronization, i.e., the tendency for MUs to discharge at, or nearly at, the same time, has often been cited as the cause for both frequency shift and amplitude increase (De Luca, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation